The removal of arsenic ion in electro-coagulation cell - Yoo, Kyoungkeun; Ji, S.; Dempsey, B. (Taylor & Francis, 2011)
The removal of As(V) and As(III) was investigated using electro-coagulation (EC) cell. Adsorption on hydro ferric oxide (HFO) generated by EC cell shows high ratio at lower pH and decreases with increasing pH. The removal efficiencies are higher in the feed solution with As(III) than with As(V). Total arsenic removal ratio is higher in the feed solution with As(III) than with As(V). Total arsenic removal ratios in EC process are over 90% at pH 4 to 9 at 1.0 A in the feed solution with As(III). At 0.5 A, As(III) adsorption ratio is 36.84% at pH 4 and total arsenic removal ratio is 60.79%, and As(III) adsorption ratio is 88.19% at pH 4 and total arsenic removal ratio is 91.13% at 1.0 A. High adsorption ratio of As(V) increases total arsenic removal ratio. In the EC cell, As(III) species could be oxidized to As(V) species, and high arsenic removal ratio is expected at low pH range by using EC process. The oxidation ratios of As(III) to As(V) are 7.1 to 41.3% and 11.1 to 27.7% at 0.5 A and 1.0 A, respectively. The EC process can oxidize As(III) to As(V), and As(V) has more affinity on HFO surface than As(III) at low pH ranges. This result suggest that this technology could be used to remove As ion from acid mine drainage. © 2011 Taylor & Francis Group, LLC.